2021
DOI: 10.1080/17510694.2021.1960705
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of creativity in independent music production

Abstract: For years, creativity has been a topic of interest for scholars in psychology, human development, and the arts. Research on creativity has produced a growing body of literature in the art and science of music production. Correspondingly, the entertainment sector has undergone what business and entrepreneurship scholars refer to as disintermediation or a reduction of skilled labor affecting the roles and responsibilities of those working in music production. Research on creativity with independent music product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…These findings also suggest that most of the Genge music production company embrace creativity in solving problems and producing music. The finding is consistent with Walzer (2020), who observed that the music production industry is characterized by gradual learning process, creativity, and experimentation that lead to the emergence of new models of music production.…”
Section: Innovation Culture In Genge Music Production Companiessupporting
confidence: 91%
“…These findings also suggest that most of the Genge music production company embrace creativity in solving problems and producing music. The finding is consistent with Walzer (2020), who observed that the music production industry is characterized by gradual learning process, creativity, and experimentation that lead to the emergence of new models of music production.…”
Section: Innovation Culture In Genge Music Production Companiessupporting
confidence: 91%
“…Published research involving the subject of autodidactism in music is scarce or absent (Ennis, 2019;Walzer, 2021;Zendel & Alexander, 2020). In respect of digital musicianship, the lack of studies can be explained in realising how commonplace self-directed and self-motivated learning processes are in this mode of creating.…”
Section: Rethinking Blended Learning With Dawsmentioning
confidence: 99%